KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBENTUK SEKOLAH BERKUALITAS DI MTS NEGERI 1 SURAKARTA - Taqiyya, Wafa’; Ali Mustofa, Triono (Jurnal Bilqolam Pendidikan Islam, 2023)
A leader plays an important role in achieving a group goal, as well as the principal who plays an important role in achieving educational goals. Principals must have excellence and professionalism in order to achieve a goal in education. Therefore, principals must play a role in many areas, starting from the preparation, inspection, and implementation processes contained in the school environment. Improving school quality is one of the goals to be achieved, so to form a quality school the principal must be able to encourage and guide educators to work expertly to improve the quality of students. The purpose of this study is to describe the leadership style applied by the principal and to find out what innovations and achievements have been made by the principal as a pioneer of education in shaping quality schools. This research uses a qualitative method with a field research approach through interviews, observations and documentation studies. The results of the study mentioned: First, the principal's leadership style at MTs Negeri 1 Surakarta uses a democratic leadership style. Second, the principal plays a lot of roles in the field of student achievement, making innovations in the curriculum and providing digital rooms, digital canteens, digital libraries and digital classes.